2018
DOI: 10.1159/000494834
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin Screening in Nodular Thyroid Disease: Is There a Definitive Answer?

Abstract: Introduction: Calcitonin (Ctn) is a hormone secreted by thyroid “C” cells and is considered an excellent marker for medullary thyroid carcinoma (MTC). However, the use of Ctn to screen patients with nodular thyroid disease (NTD) remains controversial. Objective: The aim of this work was to define the frequency of hypercalcitoninemia among NTD patients followed at a tertiary referral hospital. Methods: A retrospective analysis was made of basal Ctn measurements and corresponding patients’ records between Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…None of the trials was a case-control study. The detailed characteristics of the included studies are given in Table 1 ( 15 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ). According to the QUADAS-2 tool ( 22 , 23 ), the methodological quality of the included trials was acceptable ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the trials was a case-control study. The detailed characteristics of the included studies are given in Table 1 ( 15 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ). According to the QUADAS-2 tool ( 22 , 23 ), the methodological quality of the included trials was acceptable ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In all other studies, patients with ultrasonographically confirmed nodules irrespective of size were included. Only the retrospective analysis by Silvestre et al ( 49 ) does not specifically describe that the nodules were objectified by ultrasonography (’the exclusion criteria were absence of clinical information, and no evidence of NTD or individuals with a familial history of MTC’). In the study by Giovanella et al ( 47 ) patients who only had autonomously functioning thyroid nodules where not included.…”
Section: Methodsmentioning
confidence: 99%
“… 43 , 56 59 Numerous studies have tried to determine the exact role of routine CT measurement in cases of thyroid nodular disease. 56 61 All studies suggest that screening of thyroid nodules with serum CT measurement allows the diagnosis and treatment of MTC at an earlier stage, resulting in a better outcome compared with MTC not detected by serum CT measurement. One of the reasons for this finding is that increasing the preoperative diagnostic accuracy of MTC prompts the surgeon to perform a more radical and possibly curative treatment.…”
Section: Elevated Serum Ct Levels: Causes and Controversiesmentioning
confidence: 99%
“…We considered the possibility of using preoperative calcitonin levels as a marker of possible metastases. Current recommendations of the American Thyroid Association (ATA) advise to measure the calcitonin level in the blood serum in cases where the cytological conclusion in patients diagnosed (or suspected) of thyroid cancer and the calcitonin level may be a predictor of the disease (Wells, et al, 2015;Silvestre, et al, 2019).…”
Section: The Level Of Basal Preoperative Calcitonin As a Predictor Of Metastasesmentioning
confidence: 99%